Exploring the Impact of Bisphenol S on Lipid Storage, Behavior, and Neuronal Structure in Caenorhabditis elegans - Bozer, Ekin; Avdeev, Michael; Pandit, Bivash; Kc, Pratishna; Anaya, Maritza; Agapito, Maria (European Journal of Applied Sciences, 2026)
Bisphenol S (BPS) is a synthetic compound increasingly used as a substitute for bisphenol A (BPA) in consumer products. Despite its widespread use, growing evidence suggests that BPS may exhibit endocrine-disrupting properties similar to BPA. This study investigates the effects of BPS exposure on lipid storage, behavioral preference, and neuronal structure using Caenorhabditis elegans as a model organism. Worms were exposed to increasing concentrations of BPS and evaluated using preference assays, lipid staining, and neuronal imaging. Results demonstrate dose-dependent alterations in behavior, increased lipid accumulation, and measurable changes in neuronal morphology, suggesting that BPS is not biologically inert.